(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2025)
The fully relativistic Multi-configuration Dirac-Fock (MCDF) method within the framework of the Dirac-Coulomb Hamiltonian is employed to calculate the excitation energies and radiative rates for Li-like ions (21≤Z≤56), which includes quantum electrodynamics and Breit Corrections. We have presented energies of lowest 24 fine structural levels and radiative data for electric dipole (E1) transitions among these levels. The results have been benchmarked for a few ionic states. Comparisons are made with results compiled by NIST as well as with other results available in the Literature. We have performed analogous calculations for energy levels with the distorted wave (DW) method, in order to assess the accuracy of our results. Further, we have calculated partition functions and thermodynamic properties by using fine structure approach. We have discussed the variation of partition function, internal energy and specific heat with temperature. We strongly believe that our extensive calculations can guide experimentalists in identifying the fine-structural levels in their future works.